Intervention studies to foster resilience – A systematic review and proposal for a resilience framework in future intervention studies. (February 2018) - Chmitorz, A.; Kunzler, A.; Helmreich, I.; Tüscher, O.; Kalisch, R.; Kubiak, T.; Wessa, M.; Lieb, K.
Abstract: Psychological resilience refers to the phenomenon that many people are able to adapt to the challenges of life and maintain mental health despite exposure to adversity. This has stimulated research on training programs to foster psychological resilience. We evaluated concepts, methods and designs of 43 randomized controlled trials published between 1979 and 2014 which assessed the efficacy of such training programs and propose standards for future intervention research based on recent developments in the field. We found that concepts, methods and designs in current resilience intervention studies are of limited use to properly assess efficacy of interventions to foster resilience. Major problems are the use of definitions of resilience as trait or a composite of resilience factors, the use of unsuited assessment instruments, and inappropriate study designs. To overcome these challenges, we propose 1) an outcome-oriented definition of resilience, 2) an outcome-oriented assessment of resilience as change in mental health in relation to stressor load, and 3) methodological standards for suitable study designs of future intervention studies. Our proposals may contribute to an improved quality of resilience intervention studies and may stimulate further progress in this growing research field. Highlights: Resilience is not a stable trait, but a dynamic process. Resilience can be conceptualized as mental health in relation to stressor load. Resilience as a dynamic process of adaptation can potentially be trained. Methods and concepts used in available trainings are of limited use to assess efficacy. Suggestions for improving the quality of future intervention studies are made.